2015
DOI: 10.1016/j.jrras.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of pyocyanin pigment by Pseudomonas aeruginosa

Abstract: Sixty-three isolates belonging to the genus Pseudomonas were isolated from different environmental sources including; soil, water and clinical specimens. Twenty out of them were identified as Pseudomonas aeruginosa and individually screened for pyocyanin production. P. aeruginosa R 1; isolated from rice-cultivated soil and P. aeruginosa U 3 selected from clinical specimen (Urinary tract infection) were the highest pyocyanin producers; pyocyanin production reached 9.3 and 5.9 mg/ml, respectively on synthetic gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 37 publications
11
120
1
Order By: Relevance
“…Similar investigation was performed by E-Fouly et al 27 in which pyocyanin production from P.aeuroginosa was carried out using glycerol supplemented nutrient broth (GSNB), Mineral Medium and King's A broth and it was concluded that the production of pyocyanin was enhanced by using raw materials as nutrient sources. These results support our conclusion that the production of pyocyanin is nutrient dependent and the microbes have an advantage in synthesis of important pigments by the use of a variety of raw nutrients under varying cultivation processes 27,28 . Hence, based on our results it can be considered as a low cost chemical and natural nutrients are essential for the microbial growth and metabolism underlying the glycolysis pathway, where microbes used food for the energy to run cellular processes, thereby bestow enhanced production of pyocyanin.…”
Section: Discussionsupporting
confidence: 55%
“…Similar investigation was performed by E-Fouly et al 27 in which pyocyanin production from P.aeuroginosa was carried out using glycerol supplemented nutrient broth (GSNB), Mineral Medium and King's A broth and it was concluded that the production of pyocyanin was enhanced by using raw materials as nutrient sources. These results support our conclusion that the production of pyocyanin is nutrient dependent and the microbes have an advantage in synthesis of important pigments by the use of a variety of raw nutrients under varying cultivation processes 27,28 . Hence, based on our results it can be considered as a low cost chemical and natural nutrients are essential for the microbial growth and metabolism underlying the glycolysis pathway, where microbes used food for the energy to run cellular processes, thereby bestow enhanced production of pyocyanin.…”
Section: Discussionsupporting
confidence: 55%
“…The study of El fouly in Egypt, found that P. aeruginosa isolated from human urine sample produced more pyocyanin concentration than isolates from rice cultivated soil (production titer was 6.3 and 5.9 mg/ml, respectively) [19], While Ra'oof and Latif, in Iraq, has detected that the P. aeruginosa isolate from sputum produced the largest amount of pyocyanin (12.069 µg/ml) [29]. The study of Charyulu et al (2009), has shown that the secondary metabolite from Pseudomonas which played a significant role in lyses the pathogenic bacterial including MRSA strains [30].…”
Section: Discussionmentioning
confidence: 97%
“…While the study of Al-Imari in Baghdad/Iraq, has reported the incidence P. aeruginosa isolates from certain clinical specimens as follow: urine (22.4%), ear (18.4%), sputum (16.3%), burns (14.3%) and wounds (12.3%) [18]. El fouly and coworkers in Cairo, Egypt found that P. aeruginosa was the most common cause of urinary tract infection (12.5%), followed by burns (10%) and sputum (9%) [19]. The reasons of variations in the occurrence rates of P. aeruginosa infections may be due to underlining diseases of investigated patients, virulence factors and the local antimicrobial resistance of the organism, and other health conditions [2].…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were performed in triplicate. Pyocyanin concentration (µL/mL) was calculated as: normalP=(OD×17.072)×1.5 where OD is optical density value obtained at 520 nm, 17.072 is the extinction coefficient used to obtain the value in µg/mL, and 1.5 is the dilution factor (3 mL from initial 4.5 mL of chloroform was used) [39]. …”
Section: Methodsmentioning
confidence: 99%